The Influence of Health Education About Cadre Knowledge on Early Detection of Toddler Growth and Development at the Tamansari Health Center, Tasikmalaya City - Sri Mulyanti; Asep Setiawan; Hani Handayani; Miftahul Falah; Heri Budiawan (HealthCare Nursing Journal, 2023)
The growth and development of toddlers is one of the tasks of the central government up to the level of basic health services, namely posyandu. Where in its implementation can be carried out by trained cadres. The role of posyandu cadres is very important besides health workers, parents, cadres also play an active role in the process of monitoring growth and development. The purpose of this study was to determine the effect of health education in the implementation of stimulation of early detection of growth and development of toddlers. This study used a quantitative method with pre-experiments and used a pre-post design. Using the One-group pretest and post test design approach, the population in this study were 50 cadres representing each posyandu. The sampling technique in the study was carried out by total sampling. The instrument used to assess the knowledge of cadres is in the form of a questionnaire. The results showed that previously, more than half of the respondents had less knowledge, 26 (52%), whereas after being given health education, they experienced an increase in the good category of 38 people (76%). Wilcoxon - test obtained a p-value of 0.000 <0.05. The conclusion is that there are differences in the level of knowledge of the respondents before and after being given health education. Suggestions for health workers to strive for all posyandu to get the same visit and increase the ability of cadres to strengthen knowledge related to early detection of toddler growth and development.